Competition between photosynthesis and reproduction is constrained by leaf mass per unit area (LMA) in ferns. (21st December 2020) - Dani, K G Srikanta; Mathew, Jose; Nila-Mohan, T M; Antony, Raju; Suresh, S; Kodandaramaiah, Ullasa
Abstract: Diversity in plant life histories is primarily that found in the rate and duration of photosynthetic (vegetative) and reproductive growth. However, direct evidence for an anticipated trade-off between photosynthesis and reproduction is lacking in any plant lineage. Ferns allocate leaf space and resources to both photosynthesis and reproduction, potentially leading to competition for leaf resources between stomatal pores and reproductive spores. We hypothesized that a trade-off between stomatal density (StD; a proxy for photosynthetic capacity) and sporangial density (SpD; a measure of fertility) has evolved in monomorphic ferns due to the common space, time and resource constraints imposed by a highly conserved and globally low leaf mass per unit area (LMA) in ferns, where any increase in LMA indicated greater construction cost and longer leaf lifespan. We measured LMA, StD and SpD in 40 fern species in India that represented both monomorphic and dimorphic conditions from both terrestrial and epiphytic habits. Both StD and SpD showed a 50-fold range in monomorphic species whereas LMA was more conserved (six-fold range). LMA of terrestrial ferns was significantly lower than that of epiphytic ferns. Linear regression between LMA and StD was significantly positive in dimorphic terrestrial ferns (showing the lowest LMA among all ferns) and significantly negative in monomorphic epiphytic ferns (showing the highest LMA among all ferns). Dimorphic terrestrial ferns were highly fecund on their fertile leaves and showed a significantly higher StD to LMA ratio on their sterile leaves compared to monomorphic terrestrial ferns. Dimorphic ferns seem to maximize both StD and SpD by physical separation of photosynthesis and reproduction, and their characteristically low LMA (shorter leaf lifespan = smaller time window) potentially selects for high StD and high fertility. The regression between StD and SpD in monomorphic ferns was significantly linear and positive, although comparisons among closely related species (within families) showed negative correlations when both StD and SpD were high, captured also by a significant quadratic regression between StD and SpD in monomorphic ferns. Monomorphic terrestrial species bearing more spores per stomata showed relatively low LMA whereas those producing fewer spores per stomata possessed leaves with relatively high LMA. Monomorphic epiphytes produced as many spores as terrestrial species but showed significantly low StD for their high LMA. We discuss the evolutionary reasons behind these trends and conclude that monomorphic terrestrial ferns with high LMA (long leaf lifespan) tend to prioritize photosynthesis over reproduction, while monomorphic epiphytes (always high LMA) are significantly more fertile for lower photosynthesis. The role of LMA in framing the rules of competition between stomata and sporangia in monomorphic ferns provides a template for how photosynthesis may directly or indirectly influence reproductive strategies (and vice versa) in all land plants.